Blended Learning in Pronunciation Classroom for Higher Education: Students’ Perception - Al-Fisyar Tiara; Sukma Nur Ardini; Dyah Nugrahani (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2020)
Abstract. With skyrocketing development of online learning due to the Covid-19 outbreak, pronunciation classroom is one of the evidences that was quite affected by this pandemic situation. The controversial mindset, that this lesson needs literally face-to-face practices since they relate to organ speech's output, leads the authors into this investigation. This paper was aimed at finding out students' response toward the implementation of blended learning in pronunciation classrooms. The research design was descriptive quantitative with the population of 176 fourth semester students of English Education Department of Universitas PGRI Semarang in the academic year of 2019/2020, and 28 students coming from 4A to 4D were taken as the sample. The data were collected online through Google Form using a perception questionnaire and confirmed by phone call interview preceded by classroom observation. The data from the questionnaire were then analyzed quantitatively to determine the level of students' perception supported by descriptive data from the interviews. The results indicated that students' perception toward blended learning in the Pronunciation classroom was in the level of intermediate. Additionally, the interview revealed that the students were satisfied with blended learning implementation in Pronunciation classroom. They preferred online classes which were balanced in terms of assignment-giving and learning material. Too many assignments with fewer materials only burden the students. Therefore, the lecturers were suggested to consider their ability in handling the class, which also interests students in engaging the online classes more.Keywords: blended learning; pronunciation, higher education, students' perceptionAbstrak. Pesatnya perkembangan pembelajaran online akibat dari wabah Covid, kelas pronunciation sebagai salah satu bukti yang cukup terpengaruh oleh situasi pandemi ini. Pola pikir kontroversi, bahwa pelajaran pronunciation benar-benar membutuhkan praktik tatap muka karena berkaitan dengan luaran speech organs, sehingga mengarahkan peneliti ke permasalahan ini. Penelitian ini bertujuan untuk mengetahui respons mahasiswa terhadap penerapan blended learning di kelas pronunciation. Desain penelitian adalah deskriptif kuantitatif dengan populasi 176 mahasiswa semester IV Jurusan Pendidikan Bahasa Inggris Universitas PGRI Semarang tahun ajaran 2019/2020 dan diambil sampel 28 mahasiswa dari 4A sampai 4D. Pengumpulan data dilakukan secara online melalui google form menggunakan kuesioner persepsi dan dikonfirmasi dengan wawancara melalui telepon yang didahului dengan observasi kelas. Data dari kuesioner dianalisis secara kuantitatf didukung oleh data interview yang dianalisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa persepsi mahasiswa terhadap blended learning di kelas pronunciation berada pada level intermediate. Selain itu, hasil wawancara menunjukkan bahwa mahasiswa merasa puas dengan penerapan blended learning di kelas pronunciation. Mereka lebih menyukai kelas online yang seimbang dalam hal pemberian tugas dan materi pembelajaran. Terlalu banyak tugas dengan materi yang lebih sedikit hanya akan membebani mahasiswa. Oleh karena itu, para dosen disarankan untuk mempertimbangkan kemampuannya dalam menangani perkuliahan yang juga menarik minat mahasiswa untuk lebih banyak terlibat dalam kelas online.   Kata kunci: blended learning; pronunciation, pendidikan tinggi, persepsi mahasiswa